Please factorise x^2 -y^2 + 6y - 9 .

Asked by babai001 | 10th May, 2009, 01:47: PM

Expert Answer:

x2 -y2 +6y -9 = x2 - (y2 - 6y + 9)

                      = x2 - (y2 - 3y - 3y + 9)

                      = x2 - (y (y - 3) - 3 (y-3))

                      = x2 - (y - 3)(y-3)

                     = x2 - (y - 3)3

                     = (x + y -3) (x - y +3)                 [Using identity, a2-b2=(a+b)(a-b)]     

Answered by  | 12th May, 2009, 12:49: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.